2014
DOI: 10.1117/12.2070184
|View full text |Cite
|
Sign up to set email alerts
|

Shallow water surface gravity wave imaging, spectra and their use in shallow water dredging operations

Abstract: Imaging of shallow waters using high resolution video imagery is described. Common to mono, stereo and trinocular imaging approaches from ground and airborne platforms is the need to validate the surface water wave field measurements, particularly the amplitude and specular reflectance of water surface small gravity waves. A technique for calibration and validation of water surface gravity wave field energy spectra is described. Results demonstrate the value of video imagery where water level staff gauges with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 17 publications
(20 reference statements)
0
8
0
Order By: Relevance
“…Video imaging of bottom features such as seagrasses and sand bottom features has also been demonstrated using practical imaging techniques [16]. The imaging technique described above is being used to assist in assessing moving fluid mud and muck in Indian River Lagoon and Banana River estuarine areas and tributaries [2]. In many shallow-water estuarine regions, wind-driven gravity waves are responsible for resuspension and transport of muds and decaying organic matter within the lutocline [17,18].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Video imaging of bottom features such as seagrasses and sand bottom features has also been demonstrated using practical imaging techniques [16]. The imaging technique described above is being used to assist in assessing moving fluid mud and muck in Indian River Lagoon and Banana River estuarine areas and tributaries [2]. In many shallow-water estuarine regions, wind-driven gravity waves are responsible for resuspension and transport of muds and decaying organic matter within the lutocline [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Sonde array [20] deployment was 16-17 knots, with east winds in a shallow ≈0.7 m water column and 20-30 cm amplitude wind-driven gravity waves at the location in Banana River near Pineda Causeway [2,16] near the Atlantic Ocean in Florida (28 12 0 33.02 00 N, 80 38 0 14.72 00 W). The use of the staff gauge video imaging and Sondes shown in Figure 11 showed that the shallow-water gravity waves increase the bottom water fine particulate transport or flux of 15,071 g m À2 day À1 dry weight-nearly 450 times greater than the surface values of 13.1 g m À2 day À1 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations